2019
DOI: 10.1002/ajmg.a.61257
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic profile of patients with clinical spectrum of ambiguous genitalia, amenorrhea, and Turner phenotype: A 21‐year single‐center experience

Abstract: The aim of the present study was to determine the frequency and nature of chromosomal abnormalities involved in patients with the clinical spectrum of ambiguous genitalia (AG), amenorrhea, and Turner phenotype, in order to compare them with those reported elsewhere. The study was conducted in the Cytogenetic Department of Pasteur Institute of Morocco, and it reports on the patients who were recruited between 1996 and 2016. Cytogenetic analysis was performed according to the standard method. Among 1,415 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The overall worldwide reported prevalence of 45, XO karyotype is 40-50%, 45XO/46XX mosaicism of 15-25% and isochromosome of 10% and rest being rare karyotypes. 5,11 Mondal S et al from India reported 44.1% of classical 45, XO karyotype followed by 26.5% of isochromosomes. 12 We did not find any significant corelation of karyotype with phenotypic features in our study likely due to small study group.…”
Section: Discussionmentioning
confidence: 98%
“…The overall worldwide reported prevalence of 45, XO karyotype is 40-50%, 45XO/46XX mosaicism of 15-25% and isochromosome of 10% and rest being rare karyotypes. 5,11 Mondal S et al from India reported 44.1% of classical 45, XO karyotype followed by 26.5% of isochromosomes. 12 We did not find any significant corelation of karyotype with phenotypic features in our study likely due to small study group.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, 61.9% of our AG patients had normal karyotype, and CA was found in 38.1% of patients with AG. In a similar study conducted in Morocco, it was reported that 78.31% of patients with AG had normal karyotype, and 7.1% of patients had CAs(Elkarhat et al,2019). In other studies, CA was reported to be 4.4% in Saudi Arabia, 10.1% in Oman and 13.6% in Turkey(Balkan et al,2010;Husain and Zaki 1999;Al-Alawi et al,2016).…”
mentioning
confidence: 84%
“…Nos últimos cinco anos, os estudos de frequência das anormalidades dos cromossomos sexuais associadas a infertilidade masculina relataram que nos países do continente africano como o Moroccos, a frequência da síndrome de Klinefelter é de 2,97% de uma corte de indivíduos com infertilidade e alteração na genitália (Elkarhat et al, 2019). Já na Europa, as recentes pesquisas sob a frequência revelaram uma prevalência de 11/100 000 recém nascidos na Dinamarca (Berglund et al, 2019) Vogt et al, 1996).…”
Section: Síndrome De Klinefelterunclassified